Smart Urban Computing Applications - Jabbar, M. A. (River Publishers, 2023)
This book reports research advances in the area of deep learning, IoT and urban computing, and describes new insights based on deep learning and IoT for urban computing
Description based on publisher supplied metadata and other sources